IJMALI METHOD IN INTERPRETATION AL-QUR'AN - Wibowo, Hamid Sakti; Nurcholis, Nanang; Khurrohman, Ato'; Rohmatika, Rohmatika (TAWASUT, 2021)
AbstractCommentators who use this method usually explain the verses of the Qur'an briefly in popular language, easy to understand and easy to read. Mufasir will interpret the Qur'an directly from beginning to end. The interpretation given is not done extensively but concisely and generally so that the reader seems to be still reading the Qur'an when what is read is the interpretation. Methods are one of the most important means to achieve a set goal. In this regard, the method in the study of the interpretation of the Qur'an can be interpreted as an orderly and well thought out way to achieve a correct understanding of what God means in the verses of the Qur'an that He revealed to the prophet. Muhammad saw.Keywords: ijmali method, interpretation of the Qur'an.